Selecting persistent atrial fibrillation patients for pulmonary vein isolation based on the response to amiodarone - Benák Attila (JOURNAL OF INTERVENTIONAL CARDIAC ELECTROPHYSIOLOGY, 2019)
Pulmonary vein isolation (PVI) by catheter ablation has reduced efficacy for the treatment of persistent atrial fibrillation (persAF), as compared to paroxysmal atrial fibrillation (paroxAF). We investigated whether the selection of persAF patients for PVI who "step back" to the paroxysmal stage on amiodarone offers a success rate comparable to that of patients with paroxAF.Sixty-two consecutive persAF patients and 62 matched control patients with paroxAF were included. Persistent patients were started on amiodarone and cardioverted to sinus rhythm (SR). PVI was performed after 3 months in those who "stepped back" and had sustained SR and in all paroxAF patients.Five of the 62 (8%) study patients returned to persAF after cardioversion; despite amiodarone, they did not undergo PVI. The rest received PVI and was followed for a mean of 31 ± 14 months. Redo procedures were performed in 44% and 29% in the persAF and paroxAF group (p = 0.093), respectively. The recurrence rate after multiple procedures without antiarrhythmic drugs was similar among the persAF and paroxAF patients (11% and 7%) at 6 months (p = 0.510), but increased in the persAF group at 1 year (21% and 9%, p = 0.065) and exceeded that of the paroxAF group at the end of the follow-up (26% and 12%, p = 0.046). Kaplan-Meier survival analysis showed shorter time to recurrence in the persAF group (p = 0.045).PersAF patients who "step back" to the paroxysmal stage on amiodarone can expect long-term success of a PVI-only strategy in more than 70% of the time. However, late recurrences are more common compared to paroxAF.